PENGARUH PUASA RAMADHAN TERHADAP BERAT BADAN DAN PERSEN LEMAK TUBUH PADA MAHASISWA PROGRAM STUDI GIZI UPN "VETERAN" JAKARTA ANGKATAN 2020 DAN 2021 - Wida Ayu Nurjanah, (2023)
Background: Overnutrition is a state of unbalanced body health caused by excess fat accumulation and can interfere with health. The prevalence of overnutrition in 2013 in Indonesia at the age of more than 18 years was 13.3%. The prevalence increased in 2018 to 13.6%. Purpose: This study aims to see the effect of Ramadan fasting on body weight and percent body fat in university students. Methods: The research design used was quasi-experimental research with a one group pretest and posttest design involving 137 UPN "Veteran" Jakarta nutrition study program students, a total of 137 people. Data collection was carried out 3 times, namely before fasting, the second week of fasting and after one month of Ramadan ends. The instruments used are the BIA (Bioelectrical Impedance Analysis), Food record 24 hours and the PAL (Physical Activity Level). Data on body weight, food intake and physical activity were analyzed using the Wilcoxon test, while data on percent body fat were analyzed using a paired T test. Results: The results showed that there was a significant decrease in body weight, BMI, food intake and physical activity. There was a difference between body weight and percent body fat before fasting and body weight and percent body fat during fasting (p<0.05). There was a difference between body weight and percent body fat before fasting and body weight and percent body fat after fasting (p<0.05). There is a difference in body weight between fasting and post-fasting body weight (p<0.05). There was no difference in body fat percentage during fasting and body fat percentage after fasting (p>0.05). Conclusion: Ramadan fasting can affect body weight and percent body fat. Recommendation: Intermittent fasting can be an alternative solution for losing weight and percent body fat by paying attention to consumption of food according to balanced nutrition and active physical activity.